Endangered winter-run Chinook salmon rely on diverse rearing habitats in a highly altered landscape. (January 2018) - Phillis, Corey C.; Sturrock, Anna M.; Johnson, Rachel C.; Weber, Peter K.
Abstract: Protecting habitats for imperiled species is central to conservation efforts. However, for migratory species, identifying juvenile habitats that confer success requires tracking individuals to reproduction. Here, we used otolith strontium isotope ratios ( 87 Sr/ 86 Sr) to reconstruct juvenile habitat use by endangered Sacramento River winter-run Chinook salmon that survived to adulthood. The isotope data revealed that 44–65% of surviving adults reared in non-natal habitats, most of which is not designated as critical habitat under the Endangered Species Act. Juveniles entered these non-natal habitats at small sizes, yet left freshwater at a similar size to those that reared in the mainstem Sacramento River, suggesting these alternate rearing habitats provide suitable growth conditions. These findings indicate Sacramento River winter-run Chinook salmon rely on rearing habitats across a broader geographic region than previously known, potentially opening up greater restoration and conservation opportunities for species recovery. Highlights: Winter-run Chinook salmon are at risk of extinction primarily due to lost habitat. We find that 44–65% of surviving adults reared in non-natal habitats as juveniles. Most habitats were not previously known to be demographically important. Non-natal habitats likely provide growth and survival benefits. Protection of these critical habitats could help prevent species extinction.